Hepatic Hydrothorax in a Patient with Liver Cirrhosis: a Case Report - Martino Handoyo; Titong Sugihartono (Current Internal Medicine Research and Practice Surabaya Journal, 2021)
Hepatic hydrothorax is a transudative pleural effusion which presents in 5-10% patients with liver cirrhosis. Although fairly uncommon, it is associated with higher morbidity and lower survival rate. The mechanism is yet to be understood fully, but the most widely accepted pathogenesis involves the presence of portal hypertension, diaphragmatic defects, and negative intrathoracal pressure, all of which lead to the formation of unidirectional passage of ascitic fluid from peritoneal cavity into pleural space. Due to its origin, the pleural effusion has similar characteristics to ascitic fluid. We herein report the case of a 60-year-old woman with advanced liver cirrhosis and right-sided moderate hepatic hydrothorax. Treatment given to the patient includes diuretics, sodium restriction, and repeated thoracentesis. Subsequent evaluation of the patient revealed improvement both clinically and radiologically.